Fluorocarbyne complexes via electrophilic fluorination of carbido ligands. Issue 14 (16th March 2023) - Manzano, Richard A.; Hill, Anthony F.
Abstract : Electrophilic fluorination of lithiocarbynes affords convenient access to fluorocarbyne complexes that are prone to oxidative chlorination and coordination to gold, providing the first μ2 -fluorocarbyne. Abstract : The new fluorocarbynes [M(CF)(CO)2 (Tp*)] (M = Mo, W; Tp* = tris(dimethylpyrazolyl)borate) arise from electrophilic fluorination of the lithiocarbynes [M(CLi)(CO)2 (Tp*)] with FN(SO2 Ph)2 . The reactions of [W(CF)(CO)2 (Tp*)] with [AuCl(SMe2 )] and PhICl2 afford the first μ2 -fluorocarbyne complex [WAu(μ-CF)Cl(CO)2 (Tp*)] and the first high oxidation state fluorocarbyne [W(CF)Cl2 (Tp*)], respectively.